Pengembangan E-Modul Pembelajaran Interaktif Pada Materi Sistem Air Conditioner (Ac) Di Smk Muhammadiyah 3 Yogyakarta - aziz; subagyo; arif bintoro Johan (JURNAL VOKASI DEWANTARA (JVD), 2024)
ABSTRACT The objectives of this study are: (1) Develop and produce teaching materials E-module ac system material for class XII majoring in Automotive at SMK. (2) Knowing the feasibility of the E-module. The research method used is Research And Development (R&D) with reference to the 4D development model, namely define, design, development and dissemination. Data collection instruments are in the form of expert validation questionnaires and student questionnaires. Data analysis techniques use quantitative descriptive analysis techniques. The results of the analysis of material expert lecturers got 94.4% with the classification of "very feasible". The results of the analysis of the material expert teacher resulted in the category of "very feasible" with a percentage of 98.6% . The results of the analysis from media expert lecturers get a percentage of 88% with the category of "very feasible". The results of the trial of limited group students resulted in an "excellent" category with a percentage of 88%. Large-scale student trials resulted in the "excellent" category with a percentage of 85.5%. Based on all the results of expert assessments and student trials, the E-module of the air conditioner (ac) system is "very feasible" to be applied to help students in learning. Keywords: E-module, Interactive, Air conditioning system ABSTRAK Tujuan dari penelitian ini adalah: (1) Mengembangkan dan menghasilkan bahan ajar E-modul materi sistem AC untuk kelas XII jurusan Otomotif di SMK. (2) Mengetahui kelayakan E-modul. Metode penelitian yang digunakan adalah Research And Development (R&D) dengan mengacu pada model pengembangan 4D, yaitu define, design, development dan dissemination. Instrumen pengumpulan data berupa angket validasi ahli dan angket peserta didik. Teknik analisis data menggunakan teknik analisis deskriptif kuantitatif. Hasil analisis dosen ahli materi mendapat 94,4% dengan klasifikasi “sangat layak”. Hasil analisis guru ahli materi menghasilkan kategori “sangat layak” dengan presentase 98,6% . Hasil analisis dari dosen ahli media mendapatkan presentase 88% dengan kategori “sangat layak”. Hasil uji coba siswa kelompok terbatas menghasilkan kategori “sangat baik” dengan persentase 88%. Uji coba siswa skala besar menghasilkan kategori “sangat baik” dengan presentase 85,5%. Berdasarkan dari seluruh hasil penilaian para ahli dan uji coba peserta didik bahwa E-modul sistem air conditioner (ac) “sangat layak” untuk diterapkan guna membantu siswa dalam belajar. Kata kunci: E-modul, Interaktif, Sistem air conditioner